2008
DOI: 10.1007/s00122-008-0889-x
|View full text |Cite
|
Sign up to set email alerts
|

The development of a PCR-based marker linked to resistance to the blackcurrant gall mite (Cecidophyopsis ribis Acari: Eriophyidae)

Abstract: Gall mite (Cecidophyopsis ribis) is the most serious pest of blackcurrant (Ribes nigrum L.), causing the damaging condition known as 'big bud' and also transmitting blackcurrant reversion virus (BRV) within and between plantations. The identification of resistant germplasm is at present a time-consuming and expensive process, dependent on field infestation plots. Resistance based on gene Ce introgressed from gooseberry has been used in UK breeding programmes for blackcurrant. Using a bulked segregant analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 24 publications
1
33
0
8
Order By: Relevance
“…1 A), using a molecular marker developed by Brennan et al (2009). The analysis established that PCR product of expected size was identified in gooseberry 'Bedford Yellow' characteristic of the marker of gene Ce.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A), using a molecular marker developed by Brennan et al (2009). The analysis established that PCR product of expected size was identified in gooseberry 'Bedford Yellow' characteristic of the marker of gene Ce.…”
Section: Resultsmentioning
confidence: 99%
“…Ce gene was identified using a molecular marker based on sequence of AFLP fragment (Brennan et al 2009). Primer set 5'TTGAGACCTCCAAGTCCTGCT3' and 5'CTTGGCTTCGTTGTTAGATGC3' for PCR fragment in 180 bp length was used.…”
Section: Ce Genementioning
confidence: 99%
See 1 more Smart Citation
“…Kahu et al (2009) evaluated a number of blackcurrant cultivars in terms of productivity and berry quality, and found that some of them exhibited some resistance to the C. ribis. Brennan et al (2009) developed a PCR-based marker potentially useful for the identification of mite-resistant germplasm. They validated this marker on susceptible and resistant germplasm in the framework of blackcurrant breeding programs.…”
Section: Plant Resistancementioning
confidence: 99%
“…More than a fourth of Eriophyidae species form galls on plant leaves, buds, short stems, and flowers (Keifer et al 1982). For example, A kind of gall mite (Cecidophyopsis ribis Acari: Eriophyidae) causes the damaging condition known as "big bud" which is the most serious pest of blackcurrant (Ribes nigrum L.) (Brennan et al 2009). A. carvi Nal.…”
Section: Articlementioning
confidence: 99%